Russian WTO Accession : What Has Been Accomplished, What Can Be Expected - Tarr, David G., 1943- 1943- (The World Bank, 2007)
This paper summarizes the principal reform commitments that Russia has undertaken as part of its World Trade Organization (WTO) accession negotiations, providing detailed assessments in banking, insurance, and agriculture. The paper assesses the gains to the Russian economy from these commitments, based on a summary of several modeling efforts undertaken by the author and his colleagues. The author compares Russian commitments with those of other countries that have recently acceded to the WTO to assess the claim that the demands on Russia are excessive due to political considerations. He explains why Russian WTO accession will result in the elimination of the Jackson-Vanik Amendment against Russia. Finally, he discusses the remaining issues in the negotiations and the time frame for Russian accession as of the fall of 2007